Intertextuality and the interpretation of Psalm 1 - Botha, Phil J. (Old Testament essays, 2005)
The meaning of the word 'Torah' in Psalm 1:2 is investigated in the light of the intratextual context of Psalm 1 itself and in the light of intertextual connections of this psalm with Joshua 1, Jeremiah 17, Psalms 52 and 92, Job 8, Ezekiel 47, and 1 Chronicles 22. It is contended that 'Torah' in Psalm 1:2 refers to the Mosaic Torah rather than to the Psalter itself. The Torah of Moses is depicted in Psalm 1 as a guide on the road of life to the presence of Yahweh, symbolised by a paradise-like temple garden. The mutual connections of Psalm 1 and 1 Chronicles 22 with Joshua 1 might suggest that Psalm 1 was intended as an introduction to the first three books of the Psalter in the first place.